Effisiensi Pemanfaatan Kalsium Pada Media Budidaya Untuk Pertumbuhan Kijing Taiwan (Anodonta woodiana, LEA) - Dominggas. M. Kelabora (Berkala Perikanan Terubuk, 2014)
ABSTRACTThe purpose of this research to know the calsium content effisiencyoptimal utilization for growth Taiwanase clam (Anodonta woodiana) was carriedout in laboratory. Twenty clams with a size of 5-6 cm and a weight of 15-16grams, were reared in plastic container of 100x50x50 cm in size, contain 300 litersof fresshwater. Taiwanase clam was cultivated for 60 days with the application 4treatments and 3 replications the control without the addition of caslcium (0 ppm),the addition calcium (CaCO3) into the media as much 25 ppm, 50 ppm, 75 ppm.The result of research indicate additional calcium (CaCO3) as much 25 ppm toinside the media of cultivated consequence effeciency exploit calcium going upand fast growth the quality rate daily clam also more up. That’s also, the influencealso to the condition quality of water specialy kesadahan (alkalinitas). Asconclusion, the addition of calcium at 25 ppm into the cultivation mediumresulted efficiency calcium Taiwanase clam utilization with the value (6,22 %perday), the calcium with concentration 25 ppm in culture media constitutecalsium a which optimal and the best growth (1,10% per day).Keywords :Aquaculture; Calsium; Effisiency; growth; Taiwanase clam.